(untitled) (Research, Society and Development, 2022)
Several factors can influence the academic path and the consequences reflect on the success or challenges imposed by the post-graduate reality and in the job market. The objective of this research was to analyze the academic and professional trajectory of the graduates of the veterinary medicine course at Federal University of Fronteira Sul - UFFS, Campus Realeza/PR. The research was made with the application of a questionnaire, online, with questions about the activities and skills developed during graduation and that impacted on personal and professional life, areas of interest when joined and if they changed the choice area, questions about the professional trajectory and demands of the job market, in addition to activities not developed at graduation and that would make a difference in the professional routine. A total of 80 graduates of the veterinary medicine course at UFFS participated in this research, which represents 43.5% of graduate students. The results showed that more than half of the students failed at least two curricular components and that the reasons that contributed to the retention were mainly difficulty in adapting to the higher education model, psychological problems, and distance from the family. Almost half of the students changed their initial area of ​​interest, due to the opportunity to get to know other areas, but also depending on the demand for jobs. However, many difficulties related to personal skills were identified after training, confirming the importance of developing not only technical knowledge, but other important skills required by the job market.